Encapsulation of Bergamot Essential Oil Components in β-Cyclodextrin by Ultrasound-Assisted Co-precipitation Method: Optimization, Characterization, and Antibacterial Activity - Maraulo, Gastón Ezequiel (2024)
Bergamot essential oil (BEO) is recognized for its aroma, but also for its health benefits and potential applications. However, its use has been limited due to its volatility and tendency to degrade. Cyclodextrins have emerged as an interesting option to encapsulate and protect a wide variety of compounds. The objective of the present work was to encapsulate BEO in β-cyclodextrin (BCD) by ultrasound-assisted co-precipitation method optimized using response surface methodology (RSM) and to evaluate physical characteristics and antibacterial activity of the obtained BEO-BCD complexes. Ultrasonication time and BCD concentration were found to act synergistically, favoring complex formation. The best entrapment efficiency (near 90%) was achieved for maximum BCD concentration (15 mM), 6 min of ultrasonication, and minimum stirring time (1 h). Stirring has minimal impact on the efficiency when the process includes ultrasonication. BEO-BCD interactions were verified by differential scanning calorimetry (DSC), water sorption studies, Fourier-transform infrared and scanning electron microscopy. Isotherms were consistent with the displacement of water molecules from the BCD’s inner cavity as compounds are included. DSC showed that BEO encapsulation led to an increase in its oxidative stability. In addition, the powdered BEO-BCD combined system maintained its antibacterial capacity under the tested conditions. The results indicated that the ultrasound-assisted co-precipitation method is efficient for obtaining cyclodextrin complexes, reducing experimental times, but also avoiding the use of organic solvents. Moreover, BCD could be considered an excellent carrier to obtain antibacterial BEO in a powdered form, easy to handle and store, attractive for food industries as natural preservative.bergamot essential oil, encapsulation, ultrasonication, response65 surface methodology, β-cyclodextrin, antimicrobial activity.